Nanocarrier-based targeted drug delivery for Alzheimer’s disease: addressing neuroinflammation and enhancing clinical translation - Wang, Kang; Yang, Rongying; Li, Jing; Wang, Haitao; Wan, Li; He, Jiale (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, amyloid-beta (Aβ) aggregation, tau pathology, and chronic neuroinflammation. Among these, neuroinflammation plays a crucial role in exacerbating disease progression, making it an attractive therapeutic target. However, the presence of the blood-brain barrier (BBB) significantly limits the effective delivery of therapeutic agents to the brain, necessitating novel drug delivery strategies. Nanocarrier-based delivery systems have emerged as a promising solution to these challenges, offering targeted drug transport, enhanced BBB penetration, and improved bioavailability while minimizing systemic toxicity. This review explores the current advancements in nanocarrier-mediated drug delivery for AD, focusing on the mechanisms of neuroinflammation, the role of nanocarriers in overcoming the BBB, and their ability to modulate inflammatory pathways. Furthermore, the review discusses preclinical validation strategies and key challenges, including safety concerns, large-scale production limitations, and regulatory hurdles that must be addressed to enable clinical translation. Future perspectives emphasize the integration of nanotechnology with precision medicine, gene therapy, and artificial intelligence to optimize nanocarrier design for individualized AD treatment. By overcoming these obstacles, nanocarriers hold the potential to revolutionize therapeutic approaches for AD and other neurodegenerative diseases.